Designing of RMPA of Double Band Antenna by Modified “Interconnected SRR” Metamaterial Structure - Ms. Chanchal Tiwari; Dr. Bimal Garg (Journal of Electronic Design Engineering, 2024)
A dual band structured antenna is designed after implementing “split rectangular” shaped MTM structure on a normal patch. Initially designed antenna was operating on the frequency of 3GHz but for the application requirement metamaterial was implemented. This implemented structure not only diminished the measure of antenna but also converted it into double band antenna. Modified antenna is able to work at 2.72GHz and 2.27GHz.